PENGEMBANGAN “SEKOLAH SORE” (MADIN) DI KOTA SEMARANG (Peran, Problem dan Prospek Pengembangannya Sebagai Community College) - Abdul Kholiq (At-Taqaddum, 2013)
The reseacrh is based on the fact that the existence of afternoon school (Madrasah Diniyah or Madin) in Semarang has been more apprehensive. This condition seems to be paradox to the vision and mission of Semarang government that set the development goals in the religious city of Semarang-based Trade and Services. The purpose of this study is extracting of Madin role in supporting the achievement of national education goal, identifying Madin problem, and formulating a development model of Madin in Semarang as a college community. From this research it is known that 1) the presence of Madin in Semarang has historically been one instrument of religious culture of Semarang. 2) at the time, being Madrasah Diniyah in Semarang have encountered many problems. There are traditional management systems, curriculum and learning process which are stagnant, less up to date and quality of human resources both manager and teaching staff is relatively low and the network community as social capital of Madrasah is not managed optimally. Based on the problem above, the education development of Madrasah Diniyah in Semarang should be oriented toward: 1) improving the quality of graduates, 2) improving the quality of Madrasah Diniyahs’ education, 3) structuring better management system of Madrasah, 4) strengthening maximally the relationship with community, 5) protecting and enforcing Madin both politically and culturally from the government.